2002
DOI: 10.1007/s10142-002-0056-4
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements, genes and recombination in a 215-kb contig from wheat chromosome 5Am

Abstract: Sequencing of a contiguous 215-kb interval of Triticum monococcum showed the presence of five genes in the same order as in previously sequenced colinear barley and rice BACs. Gene 2 was in the same orientation in wheat and rice but inverted in barley. Gene density in this region was 1 gene per 43 kb and the ratio of physical to genetic distance was estimated to be 2,700 kb cM -1 . Twenty more-or-less intact retrotransposons were found in the intergenic regions, covering at least 70% of the sequenced region. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
160
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 46 publications
15
160
0
Order By: Relevance
“…This result agreed with previous observations for T. tauschii (Moullet et al 1999) and other monocot species (Woo et al 1994;Zhang et al 1996;Tomkins et al 1999) that suggested a higher frequency of NotI restriction sites relative to dicot species. This result was also expected based on the higher GC content of the wheat genome (45.7%; SanMiguel et al 2002) and the GCGGCCGC recognition sequence of NotI.…”
Section: Characterization Of the Durum Wheat Bac Librarysupporting
confidence: 75%
See 4 more Smart Citations
“…This result agreed with previous observations for T. tauschii (Moullet et al 1999) and other monocot species (Woo et al 1994;Zhang et al 1996;Tomkins et al 1999) that suggested a higher frequency of NotI restriction sites relative to dicot species. This result was also expected based on the higher GC content of the wheat genome (45.7%; SanMiguel et al 2002) and the GCGGCCGC recognition sequence of NotI.…”
Section: Characterization Of the Durum Wheat Bac Librarysupporting
confidence: 75%
“…3 Assignment of Langdon (LDN) BAC clones selected with the HMW-glutenin probe to the A or B genome using chromosome substitution lines Langdon 1D(1A) and Langdon 1D(1B). Genomic DNA and BAC clones were digested with the restriction enzyme TaqI requirement for chromosome walking in wheat because large regions of repetitive elements are present, even in gene-rich regions (SanMiguel et al 2002). The average insert size of this library (131 kb) was larger than the average insert size of previous published Triticeae BAC libraries (T. tauschii, 119 kb; T. monococcum, 115 kb; H. vulgare, 106 kb) and the proportion of clones with cpDNA or no inserts was reduced to very low levels (<2%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations